1-(5-Carboxyindazol-1-yl)propan-2-ones as dual inhibitors of cytosolic phospholipase A2α and fatty acid amide hydrolase: bioisosteric replacement of the carboxylic acid moiety. (1st November 2016) - Althaus, Jan; Hake, Theresa; Hanekamp, Walburga; Lehr, Matthias
Abstract: Indazole-5-carboxylic acids with 3-aryloxy-2-oxopropyl residues in position 1 were previously reported to be potent dual inhibitors of cytosolic phospholipase A2 α (cPLA2 α) and fatty acid amide hydrolase (FAAH). In continuation of our structure-activity studies on cPLA2 α and FAAH inhibitors, a number of derivatives of these substances characterized by bioisosteric replacement of the carboxylic acid functionality by inverse amides, sulfonylamides, carbamates and ureas were prepared. The biological evaluation of the obtained compounds showed that the carboxylic acid functionality of the lead compounds is of special importance for a pronounced inhibition of cPLA2 α and FAAH.